A review of the biology, distribution patterns and management of the invasive species Amaranthus palmeri S. Watson (Palmer amaranth): Current and future management challenges. (8th December 2021) - Roberts, Jason; Florentine, Singarayer
Abstract: Amaranthus palmeri S. Watson (Palmer amaranth) is an invasive agricultural weed that has quickly risen from a state of relative obscurity to now being globally regarded as one of the most economically destructive and difficult to manage weed species. It is now found in more than 45 countries where it poses a serious threat to agricultural production systems. Amaranthus palmeri is known to aggressively compete against crop plants for resources such as light, space, nutrients and soil moisture, all of which can result in significant crop yield reduction or even lead to crop failure. It has also been reported that A. palmeri is highly prone to evolve herbicide resistance; this makes management exceedingly challenging. Whilst there have been several control approaches introduced to manage the spread and impact of A. palmeri, many of them require more specific and focused research for their successful local and widespread application. In this regard, this global review explores the species' biology and global distribution patterns, together with previous and current management strategies. It also explores and identifies promising areas of research that still require further investigation to more confidently assist in the control and containment of this globally concerning weed.